Time, Cost, Information Seeking Skills and Format of Resources Present Barriers to Information Seeking by Primary Care Practitioners in a Research Environment - Preddie, Martha Ingrid (Evidence Based Library and Information Practice, 2007)
Objective – To determine the information seeking behaviors of primary care practitioners in order to inform future efforts towards the design of information services that would support quality in primary care. Design – A cross-sectional survey. Setting – A primary care practice based research network (PBRN) of caregivers who serve a broad population while simultaneously studying and disseminating innovations aimed at improvements in quality, efficiency and/or safety of primary health care in the United States. Subjects – All primary care practitioners in the PBRN including family practitioners, general practitioners, nurse practitioners and physician assistants. Methods – A questionnaire comprising twenty-six questions was distributed to 116 practitioners. Practitioners attached to academic centres (who were also members of the PBRN) were excluded in order “to achieve a sample of practices more representative of the primary care practising population” (208). Descriptive data were collected and analyzed. SPSS v11.5 was used for statistical analyses. Main results – There was a response rate of 51% (59 of 116). Fifty-eight percent of the respondents stated that they sought information (excluding drug dosing or drug interactions information) to support patient care several times a week. Sixty-eight per cent sought this information while the patient waited. Almost half of the respondents had access to a small medical library (48%) or a hospital library (46%), while 21% used a university medical library. Approximately 14% had no immediate access to a medical library. Almost 60% of practitioners stated that they had an e-mail account. Thirty-four percent agreed that the use of e-mail to communicate with patients enhanced medical practice, while 24% disagreed. There was frequent prescribing of Internet-based consumer health information to patients by only 16% of the practitioners, while Internet support groups were frequently recommended by 5%. The main barriers to information seeking were lack of time (76%), cost (33%), information seeking skills (25%), and format of information sources (22%). The use of EBM resources was fairly low, while there was a high preference for ready reference and interpersonal sources. When compared with print information resources, the use of online resources was moderate. A significant correlation was found between use of online sources and use of print sources, namely, that practitioners who used online sources more frequently, also sought information from print sources more frequently, with the inverse being true for those who sought information less frequently from either electronic or print sources. Conclusion – Primary care practitioners in this rural PBRN used print and interpersonal sources more than online sources. Practitioners who are more likely to use print sources are also more likely to seek online information. Librarians working in PBRN environments will need to identify interventions that address barriers such as time, cost, and information-seeking skills.